The definitive word on Michael Jordan - Barkley, Charles, 1963-; Erving, Julius (Dallas, TX : Beckett Publications, 1998)
This book covers all facets of MJ's life through insight from his closest friends and intense rivals and through the works of the NBA's most talented photographers.
Air Jordan / Spike Lee -- The player / Jerry West -- The leader / Phil Jackson -- The kid / Fred Lynch -- The shot / Sam Perkins -- The rookie / Kevin Loughery -- The competitor / Charles Barkley -- The CEO / Pat Riley -- The legacy / Magic Johnson.
Keywords: Jordan, Michael, -- 1963-; Jordan, Michael, -- 1963-; Jordan, Michael, -- 1963-; Basketball players -- United States -- Biography; Basketball players; United States; Basketball players -- United States -- Biography; biography -- sports; biography; Biographies; Biography; Biographies